Variability of eclipse timing: the case of V471 Tauri. Issue 4 (3rd October 2022) - Kundra, Emil; Hambálek, Ľubomír; Vanaverbeke, Siegfried; Dubovský, Pavol; Logie, Ludwig; Rau, Steve; Dubois, Franky
ABSTRACT: The post-common envelope binary V471 Tauri has been an object of interest for decades. V471 Tau shows various phenomena due to its evolutionary state and unique properties, e.g. its magnetic accretion and eclipse timing variation (ETV). Previous authors explained the ETVs by different sometimes contradictory theories. In this paper, we present and analyse the variability of the eclipse timing of this star. We observed V471 Tauri over the last 10 yr and covered the second cycle of its period variation. Based on our analysis of the presented data, we assess the possible existence of a brown dwarf in this system and derive its orbital parameters. We compare the results of our dynamical modelling to the solution predicted by Applegate-mechanism theories, which have been developed in recent studies. We found that the observed ETV cannot be explained only by the presence of additional components to the binary.